2007
DOI: 10.1002/app.27048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoclay on properties of HDPE/wood composites

Abstract: Composites based on high density polyethylene (HDPE), pine flour, and organic clay were made by melt compounding and then injection molding. The influence of clay on crystallization behavior, mechanical properties, water absorption, and thermal stability of HDPE/pine composites was investigated. The HDPE/pine composites containing exfoliated clay were made by a two-step melt compounding procedure with the aid of a maleated polyethylene (MAPE). The use of 2% clay decreased the crystallization temperature (T c )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
156
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(172 citation statements)
references
References 43 publications
(69 reference statements)
13
156
0
3
Order By: Relevance
“…The incorporation of 2 phc OMMT led to the increase in the flexural strength and modulus about 37 and 29%, respectively. The significant improvement in the flexural properties was related to the large aspect ratio and high interfacial contact area of the nanoparticles [10,[12][13][14][15][16][18][19][20][21][22]. As it can be clearly seen from Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 79%
See 2 more Smart Citations
“…The incorporation of 2 phc OMMT led to the increase in the flexural strength and modulus about 37 and 29%, respectively. The significant improvement in the flexural properties was related to the large aspect ratio and high interfacial contact area of the nanoparticles [10,[12][13][14][15][16][18][19][20][21][22]. As it can be clearly seen from Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 79%
“…This increment in the tensile properties was mainly attributed to the reinforcing effect of OMMT with high aspect ratio [10,[12][13][14][15][16]. It was expected that strong interfacial adhesion between polymer matrix and nanoparticles efficiently transferred the stress and improved the mechanical properties [18][19][20][21][22].…”
Section: Mechanical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The effective use of wood-based particles as fillers or reinforcements in the thermoplastic polymers requires a fundamental understanding of the stability of the composite materials. The majority of lignocellulosic fillers have low degradation temperatures (*200°C), which make them inadequate for processing with thermoplastics with processing temperatures above 200°C [36][37][38]. Decomposition of wood components, such as cellulose and lignin creates voids inside the composite, causing reduction of the mechanical properties [39].…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been shown that in order to estimate the thermo-oxidative stability of the composite materials, it is necessary to take into account the oxidation induction time (OIT) [40][41][42]. OIT values depend on factors such as density, temperature, physical and chemical properties of polymer, type and amount of cellulosic fillers [38]. However, analysis of literature data has revealed many controversies; often the use of the same modifications of the lignocellulose component would bring different results.…”
Section: Introductionmentioning
confidence: 99%